Effects of Fe 3O 4 nano particles addition in high temperature superconductor YBa 2Cu 3O 7-? - Abd-Ghani S.N.; Abd-Shukor R.; Kong W. (2023)
The effects of nano particles Fe3O4 addition on the superconducting and transport properties of YBa 2Cu 3O 7-? (YBCO) were studied. YBa 2Cu 3O 7-? superconductor powders were prepared by using high purity oxide powders via solid state reaction method. Nano Fe 3O 4 with 0.01 - 0.05 wt.% with average size 28 nm was added into YBCO. The transition temperatures (T c) of the samples were measured by using four point probe method. The critical current (I c) of the samples has been determined by using the 1 ? V/cm criterion from 30 - 77 K. Sample with 0.02 wt.% nano Fe 3O 4 showed the highest T c at 87 K. It is interesting to note the same sample also exhibited the highest J c at 77 K up to 1683 mA/cm 2. Nano Fe 3O 4 has acted as effective flux pinning centers in YBCO. A small amount of nano particles Fe 3O 4 addition has successfully improved the superconducting and transport properties of YBCO. The excessive addition of nano Fe 3O 4 (> 0.02 wt.%) suppressed the T c and J c. Overall, J c decreases with increasing temperature (30 - 77 K) as a consequence of thermally activated flux creep. Magnetic impurities normally suppress superconductivity. However, by adding magnetic nano particles, current carrying capacity of superconductors YBCO was enhanced significantly. (2012) Trans Tech Publications.